2012
DOI: 10.2337/dc11-1288
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular and All-Cause Mortality: Impact of Impaired Health-Related Functioning and Diabetes

Abstract: OBJECTIVE There is an established link between health-related functioning (HRF) and cardiovascular disease (CVD) mortality, and it is known that those with diabetes predominantly die of CVD. However, few studies have determined the combined impact of diabetes and impaired HRF on CVD mortality. We investigated whether this combination carries a higher CVD risk than either component alone. RESEARCH DESIGN AND METHODS The Australian Diabetes, Obesity and Lifestyle (AusDiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
(52 reference statements)
5
24
1
3
Order By: Relevance
“…Although these findings are similar to what have been reported in the literature [6,28], they should be taken with caution, as the subscales are highly correlated with one another, and hence their effects are not independent.…”
Section: Discussionsupporting
confidence: 90%
“…Although these findings are similar to what have been reported in the literature [6,28], they should be taken with caution, as the subscales are highly correlated with one another, and hence their effects are not independent.…”
Section: Discussionsupporting
confidence: 90%
“…For external validation, we used data from the Australian Diabetes, Obesity and Lifestyle Study (AusDiab)27 28 including participants aged 45–65 at baseline (1999/2000) with available disability information at follow-up (2011/2012) or died before 30 November 2012 (n=2182; mean age 55, 47% men). Disability at follow-up was defined as having some difficulty to at least one of eating, bathing, dressing, transferring and toileting.…”
Section: Methodsmentioning
confidence: 99%
“…The ZODIAC-18 study of type 2 diabetes patients from the Netherlands reported that a 10-point increase on the PCS decreased the risk for mortality by approximately 10% [Landman 2010]. The AusDiab study reported that those with a co-occurrence of diabetes and impaired PCS had an almost three-fold increase in cardiovascular mortality compared to those with diabetes and with average physical functioning [Williams 2012]. …”
Section: Discussionmentioning
confidence: 99%
“…Subjective health status, including self-reported physical functioning, may be a marker for increased risk of mortality as well [Jylha 2009; McEwen 2009; Landman 2010]. The prospective AusDiab and ZODIAC-18 studies, conducted in Australia and the Netherlands, respectively, reported that the co-occurrence of diabetes and poor self-rated physical functioning was associated with increased risk of mortality [Landman 2010; Williams 2012]. However, it is unclear if this association exists in the United States or differs by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%